Evaluation of sterile glove usage on digital tactile sensitivity using the Grating Orientation Task - Riegel, Thomas O.; Zellner, Eric M.; Hedlund, Cheryl S.; Kraus, Karl H. (Frontiers in Veterinary Science, 2024)
Introduction: Surgical glove use may be associated with a decrease in tactile sensitivity, with thicker gloves or double-gloving techniques further altering sensation. This study evaluates digital tactile sensitivity by use of a Grating Orientation Task (GOT) with multiple sterile gloving techniques (no gloves, single standard gloving, double standard gloving, orthopedic gloves, and micro-thickness gloves).Methods: Each participant performed the GOT at increasing grating widths until correctly noting orientation in ≥8 of 10 trials with multiple glove types or double-gloving technique. Glove order was randomly assigned and participants were blinded to the orientation and dome size.Results: All gloves except micro-thickness gloves showed increased threshold sensitivity values (i.e. worse fingertip sensitivity) when compared to control (micro:control, p=0.105, others:control, p<0.05).Single-layer gloves showed no significant difference in sensitivity when compared to orthopedic (p=0.06) or double-layer latex gloves (p=0.26).Discussion: Standard latex gloves decreased fingertip sensitivity when evaluated with the GOT. Double-layer and orthopedic latex gloves do not decrease sensitivity when compared with single-layer gloving. Micro-thickness gloves may provide similar tactile sensitivity to no surgical glove.